Reflectivity and topography of cells grown on glass-coverslips measured with phase-shifted laser feedback interference microscopy - Atılgan, Erdinç (Optical Society of America, 2011)
In spite of the advantages associated with the molecular specificity of fluorescence imaging, there is still a significant need to augment these approaches with label-free imaging. Therefore, we have implemented a form of interference microscopy based upon phase-shifted, laser-feedback interferometry and developed an algorithm that can be used to separate the contribution of the elastically scattered light by sub-cellular structures from the reflection at the coverslip-buffer interface. The method offers an opportunity to probe protein aggregation, index of refraction variations and structure. We measure the topography and reflection from calibration spheres and from stress fibers and adhesions in both fixed and motile cells. Unlike the data acquired with reflection interference contrast microscopy, where the reflection from adhesions can appear dark, our approach demonstrates that these regions have high reflectivity. The data acquired from fixed and live cells show the presence of a dense actin layer located ≈ 100 nm above the coverslip interface. Finally, the measured dynamics of filopodia and the lamella in a live cell supports retrograde flow as the dominate mechanism responsible for filopodia retraction.